Vključevanje multikulturnih vsebin ameriških (zvezna država Kansas) razrednih učiteljev v poučevanje - Lunder Verlič, Stanka (Revija za elementarno izobraževanje, 2014)
Integrating Multicultural Subject Matters into Teaching Strategies of Elementary School Teachers (The U.S. State of Kansas). The following academic article is based on a PhD thesis that is currently being completed, titled Education and Qualifications of Elementary School Teachers in the U.S. State of Kansas and Slovenia for teaching in classes with immigrant children. The research study titled Integrating Multicultural Subject Matters into Teaching Strategies of Elementary School Teachers (The U.S. State of Kansas), conducted in 2007 based on a sample of 89 elementary school teachers in the U.S. State of Kansas, represents one aspect of assessing the adequacy of undergraduate education regarding multicultural subject matters for elementary school teachers in Slovenia and the U.S. (State of Kansas) as well as the qualifications of elementary school teachers of both countries for working with immigrant children. Despite the long-standing tradition of multicultural education in western countries, the research results for Kansas elementary school teachers showed a presence of significant discrepancies between the actual and optimal integration of multicultural subject matters. These results indicate that future undergraduate study programs will have to invest more time in developing multicultural skills and providing practical experiences for working in a diverse environment.
Keywords: multicultural education; elementary school teacher; undergraduate study program; immigrant children